Functional Assemblages of Collembola Determine Soil Microbial Communities and Associated Functions - Coulibaly, Sékou F. M.; Winck, Bruna R.; Akpa-Vinceslas, Marthe; Mignot, Laurent; Legras, Marc; Forey, Estelle; Chauvat, Matthieu (Frontiers in Environmental Science, 2019)
Soil processes such as decomposition are mainly performed by soil biota. Although soils worldwide are extremely biodiverse, the relationship between decomposers (fauna and microorganisms), and ecosystem function is poorly understood. Collembola are abundant and ubiquitous microarthropods that are found in terrestrial ecosystems. They can affect the amount of biomass and the activity of microbial communities, either directly through selectively feeding on fungi and bacteria, or indirectly by dissemination of microbial propagules, and the alteration of nutrient availability. However, despite the functional role they play in belowground food webs, the interactions between natural assemblages of soil microbes and Collembola receive little attention. This study, conducted in microcosm conditions, examines the effects of two distinct natural assemblages of functional groups of Collembola (ep- and euedaphic) upon microbial communities using PLFA markers and their associated soil functions (e.g., enzymatic activities and C mineralization rate) over a 2-month period. Our principal objective was to determine whether different functional groups of Collembola had varying effects on microbial soil community abundance, structure and activity, resulting in potentially important effects on ecosystem processes. Our findings show that the interactions of the functional groups of Collembola with microbial communities vary significantly whether they are alone or combined. A distinct response in the composition of the microbial communities was found at the end of the 2-month period. The communities were significantly different from each other in terms of PLFA marker composition. We found that the epedaphic species were related to and promoted Gram+ bacteria whereas euedaphic species were related to Gram- bacterial markers. This had further repercussions on soil function, such as nutrient recycling. Combining both functional groups did not lead to a complementary effect on soil microbial properties, with a drastically different outcome between the first and the second month of the experiment. Additional research dealing with the interactions between decomposers using natural assemblages will help to predict the functional outcomes of soil biota structure and composition.